2013
DOI: 10.1002/pssr.201308069
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy dominant strong visible photoluminescence from BiFeO3 nanotubes

Abstract: In this Letter, we report oxygen vacancy dominant strong visible photoluminescence (PL) from multiferroic BiFeO3(BFO) nanotubes (NTs) prepared by sol–gel template method. Abundant oxygen vacancies present in BFO NTs provide alternate paths for the photo‐induced carrier generation and recombination thus affecting the PL and photoabsorption characteristics. This study not only assists in understanding the optoelectronic characteristics of BFO NTs at nanoscale but also suggests BFO nanostructures as potential can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…These oxygen vacancies exist in three charged states: singly charged (V O+ ), doubly charged (V O++ ), and neutral (V O ). It should be noted that the emission wavelength closely matches with our previously reported results . However, the variation in relative intensity and slight shift of the defect emission is probably due to sample‐to‐sample variations in the depth of defect states (energy of defect sites) due to small size and shape variation of BFO nanostructures.…”
Section: Table Summarizing Activation Energies For Negative Thermal Qsupporting
confidence: 89%
See 1 more Smart Citation
“…These oxygen vacancies exist in three charged states: singly charged (V O+ ), doubly charged (V O++ ), and neutral (V O ). It should be noted that the emission wavelength closely matches with our previously reported results . However, the variation in relative intensity and slight shift of the defect emission is probably due to sample‐to‐sample variations in the depth of defect states (energy of defect sites) due to small size and shape variation of BFO nanostructures.…”
Section: Table Summarizing Activation Energies For Negative Thermal Qsupporting
confidence: 89%
“…It should be noted that the emission wavelength closely matches with our previously reported results. [8,10,33] However, the variation in relative intensity and slight shift of the defect emission is probably due to sample-to-sample variations in the depth of defect states (energy of defect sites) due to small size and shape variation of BFO nanostructures. Different depths of defect states (energies of defect states) are reflected through small difference in the spectral positions of emission maximums.…”
Section: Wide-bandgap Semiconductor Nanowires With Surface Defect Emimentioning
confidence: 99%
“…It has a bandgap varying from 2.5 eV to 2.8 eV [5][6][7]. It has been investigated as a potential candidate for optoelectronic applications such as photovoltaics [8][9][10], photonic and optoelectronic devices [11,12]. Studies have shown that the photoluminescence properties of BFO can even be manipulated through the use of electric fields [13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the photoluminescence properties of BFO can even be manipulated through the use of electric fields [13]. Further, the optoelectronic properties of BFO have been found to be enhanced in one dimensional nanostructures such as nanofibers [11] and nanotubes [12] when compared to bulk samples, due to strong surface level interactions and large surface to volume ratio [14]. Electrospun nanofibers have added advantages over other one dimensional nanostructures such as high aspect ratios, large surface areas [15][16][17] and enhanced optical properties [11,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation